The Implication of Caspian Basin Energy Politics Towards The Establishment of The United States Energy Security in Caspian Region - Annisa Mahasti; Ade Wirasenjaya (Dauliyah: Journal of Islam and International Affairs, 2024)
The energy politics of Caspian basin as its resources has become one of the main sources for world energy supplies has successfully provided beneficial for regional, national and international business area since the discovery of the myriad of oil and gas in the early 1990s after the dissolution of Soviet Union. Ever since, Caspian basin has appeared to be a source for international political and economic competitions and has appealed many states including the United States of America to its energy politics competition. This research tried to explain the implication that Caspian basin energy politics has brought to the establishment of the United States energy security through the lenses of securitization theory. This theory explained how the United States built its energy securitization in Caspian basin region through Speech Act that lied within Clinton and Bush’s Administration Strategic Thinking and Foreign Policy by the establishment of alliances from states inside and outside the region.  Keywords: Caspian Basin, Energy Politics, Energy Resources, Energy Securitization Theory, Foreign Policy, Speech Act, United States.